A Discourse Analysis of English Articles Introducing Festivals in the United Kingdom - Trần Thị Mỹ Trung (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study is aimed at conducting a discourse analysis of English articlesintroducing festivals in the United Kingdom in light of Halliday‘s FunctionalGrammar, considering clauses in the articles as representation, exchange andmessage, thereby widening the researcher‘s knowledge about how to applyFunctional Grammar to the analysis of discourse